Impact Des Facteurs Intersubjectifs Sur L’engagement Des Cadres Ivoiriens Au Développement De Leur Localité d’Origine - Inoussa, Daboné; Zoumana, Méité (European Scientific Journal, ESJ, 2018)
Despite the policy of developing localities initiated by the Ivorian state, disparities between rural and urban populations are still obvious. The lack of interest in this process of development from localities’ native executives is highlighted. The present survey tempts to examine this lack of personal commitment from executives in relation with intersubjective factors such as sympathy, autonomy, mystical practices and communication. In so doing, a sample of 121 executives from the Ivorian public administration are selected rationally in the purpose of data collection through a questionnaire. Statistical analysis indicate that, except the autonomy to bring innovations in rural areas, the targeted intersubjective factors have a significant impact on the executives’ level of commitment in their locality’s development. As regards to practical repercussions, these results underline the necessity to develop the local populations’ mind of sympathy and communication towards their executives. Local populations have also to put an end to any mystical practice able to frighten their native executives if they want them to fully take part in the development of their different localities.